Teachers as Facilitators Integrating Social Network Technology into a 21st Century Classroom in an International School in Kuala Lumpur - Kunasunthary Duraippah; Ong , Peter
The objective of this study is to comprehend how teachers prepare their students for 21st-century learning using social networking technology. Data in this research was collected through observations and interviews. The interviews were structured and comprised open-ended questions. The data was analysed using qualitative methods. Six teachers from an international school in Kuala Lumpur were interviewed in this research: two teachers from its kindergarten, two teachers from its junior school, and two teachers from its senior school. The findings showed that the teachers had integrated social network technology in creating a 21st-century classroom. The use of technology helped them to transform teaching in their classrooms. It helped them to prepare their students for the global digital transformation taking place at present. Integrating social network with 21st-century learning in the classroom benefited both the teachers and students. Most of the social network applications are easy to use. Once a week, the teachers attended technical professional development training organised by information technology specialists and technicians to upgrade their skills and learn to use the latest devices and applications in order to support the transformation of their role towards learner-centred 21st-century learning. (Abstract by authors)